Sociodemographic, Health, and Lifestyle-Related Characteristics Associated With the Commencement and Completion of a Web-Based Lifestyle Educational Program for People With Multiple Sclerosis: Randomized Controlled Trial - Jeanette Reece; Maggie Yu; William Bevens; Steve Simpson-Yap; Rebekah Davenport; George Jelinek; Sandra Neate (JMIR Publications, 2024)
BackgroundDigital health interventions increase access to multiple sclerosis (MS)-related knowledge for people living with MS; however, our understanding of factors associated with engagement in web-based learning is limited. ObjectiveThis study aims to examine associations between participant sociodemographic, health, and lifestyle-related characteristics and the commencement and completion of the Multiple Sclerosis Online Course (MSOC) in a randomized controlled trial (RCT). MethodsAn intervention course was developed based on the Overcoming MS Program-an evidence-based lifestyle modification program for MS, and a standard care course was developed based on international MS website information. An RCT was conducted to compare the effectiveness of the intervention course versus the standard care course in improving health outcomes in people living with MS. Participant data were collected from a baseline survey. Associations between baseline participant characteristics and MSOC commencement and completion, respectively, were assessed using multivariate log-binomial regression. ResultsOverall, 1893 participants enrolled in the RCT, and 45.27% (n=857) completed the baseline survey: 23.5% (n=444) in the intervention course and 21.8% (n=413) in the standard care course. Of these 857 participants, 631 (73.6%) commenced the standard care course or intervention course, and 49.1% (218/444) and 54.2% (224/413) completed the intervention course and standard care course, respectively. University education, partnered relationship status, and higher mental and physical quality of life were associated with 19%, 12%, 20%, and 22% higher rates of course commencement, respectively. Clinically significant fatigue was associated with a 10% reduction in the likelihood of commencement. Strongest associations with intervention course completion included middle and older adulthood, male sex, fatigue, and preexisting adherence to a diet program, with 96%, 27%, 24%, and 19% higher rates of completion observed, respectively, whereas higher self-efficacy was associated with up to 35% lower intervention course completion. Associations with standard care course completion included practicing meditation (20% higher completion), whereas employment was associated with 22% lower completion. ConclusionsSociodemographic and clinical factors, as well as lifestyle-related factors, were important factors in MSOC commencement and completion. These data may help guide the design and enhancement of digital health interventions tailored for people living with MS. Trial RegistrationAustralian New Zealand Clinical Trials Registry ACTRN12621001605886; https://tinyurl.com/2vyve9p9 International Registered Report Identifier (IRRID)RR2-10.1186/s12883-023-03298-0